Anti‐inflammatory and anti‐endotoxin properties of peptides derived from the carboxy‐terminal region of a defensin from the tick Ornithodoros savignyi. (10th December 2015) - Malan, Melissa; Serem, June C.; Bester, Megan J.; Neitz, Albert W. H.; Gaspar, Anabella R. M.
Abstract : Antimicrobial peptides are small cationic peptides that possess a large spectrum of bioactivities, including antimicrobial, anti‐inflammatory and antioxidant activities. Several antimicrobial peptides are known to inhibit lipopolysaccharide (LPS)‐induced inflammation in vitro and to protect animals from sepsis. In this study, the cellular anti‐inflammatory and anti‐endotoxin activities of Os and Os‐C, peptides derived from the carboxy‐terminal of a tick defensin, were investigated. Both Os and Os‐C were found to bind LPS in vitro, albeit to a lesser extent than polymyxin B and melittin, known endotoxin‐binding peptides. Binding to LPS was found to reduce the bactericidal activity of Os and Os‐C against Escherichia coli confirming the affinity of both peptides for LPS. At a concentration of 25 µM, the nitric oxide (NO) scavenging activity of Os was higher than glutathione, a known NO scavenger. In contrast, Os‐C showed no scavenging activity. Os and Os‐C inhibited LPS/IFN‐ γ induced NO and TNF‐ α production in RAW 264.7 cells in a concentration‐dependent manner, with no cellular toxicity even at a concentration of 100 µM. Although inhibition of NO and TNF‐ α secretion was more pronounced for melittin and polymyxin B, significant cytotoxicity was observed at concentrations of 1.56 µM and 25 µM for melittin and polymyxin B, respectively. In addition, Os, Os‐C and glutathione protected RAW 264.7 cells from oxidative damage at concentrations as low as 25 µM. This study identified that besides previously reported antibacterial activity of Os and Os‐C, both peptides have in addition anti‐inflammatory and anti‐endotoxin properties. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Synthetic peptide Os and its analogue Os‐C were found to bind LPS and to inhibit LPS‐induced TNF‐ α and NO production by RAW 264.7 cells. In addition, Os was able to scavenge NO directly and in RAW 264.7 cells both peptides displayed antioxidant activity. This study identified Os and Os‐C as multifunctional peptides that besides having antibacterial activity possess anti‐endotoxin and anti‐inflammatory properties and may attenuate tissue injury by scavenging free radicals.